Analysis Comparison Of Earnings Between Farmer of Coffee Which Processing by Using Pulper Coffee and With Way of Traditional in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District - Resdianto, Tri; Batubara, Marli; Iswarini, Harniatun (Universitas Muhammadiyah Palembang, 2015)
Analysis Comparison Of Earnings Between Farmer of Coffee Which Processing by Using Pulper Coffee and With Way of Traditional in Tangga Rasa Village Sikap Dalam Sub District Empat Lawang District